Correlation between discharge readiness and uncertainty in illness among parents with preterm infants hospitalized in NICU (NICU早产儿父母出院准备度与疾病不确定感的相关性分析) - TAN Jilei (谭继磊); WEI Qin (韦琴); LIANG Jie (梁洁); LIANG Hua (梁华); TENG Xiaoyun (滕小芸); TANG Lihua (唐利华); SONG Jingwen (宋静雯); HE Ting (何婷) (中西医结合护理)
Objective To investigate the correlation between discharge readiness and uncertainty in illness among parents with preterm infants hospitalized in NICU, so as to provide a reference for clinical training. Methods Totally 75 parents with preterm infants were investigated using Readiness for Hospital Discharge Scale-Parent Form (RHDS-FM) and Parents’ Perception of Uncertainty Scale-Family Member(PPUS-FM). Results The total score of uncertainty in illness and discharge readiness were (95. 73±13. 49) and (132. 04±25. 85) respectively, 54. 67%(41/75) of the parents believed that they were not ready for discharge; and the discharge readiness was negatively correlated with the uncertainty of illness (r= -0. 346, P<0. 01). Conclusion The discharge readiness and illness uncertainty of parents of premature infants are both at a moderate level, and they are closely related. The higher the discharge readiness , the lower the illness uncertainty. Therefore, medical staff should pay close attention and evaluate the discharge readiness and illness uncertainty of the parents of premature infants, and provide timely information support, especially care knowledge and plans, to change parents' abnormal cognition, and prepare premature infants and their parents for a smooth transition to the family. (目的 了解早产儿父母出院准备度与疾病不确定感的现状及其相关性, 为临床提供参考依据。方法 采用一般资料调查表、出院准备度量表-父母版(RHDS-FM)及疾病不确定感量表-父母版(PPUS-FM)对新生儿科75例早产儿的父母进行调查。结果 早产儿父母出院准备度总分为(132. 04±25. 85)分, 54. 67%(41/75)的父母认为未做好出院准备, 疾病不确定感总分为(95. 73±13. 49)分, 出院准备度与疾病不确定感呈负相关(r=-0. 370, P＜0. 01)。结论 早产儿父母的出院准备度与疾病不确定感均处于中等水平, 两者密切相关, 出院准备度越高, 疾病不确定感越低。医护人员应密切关注并评估早产儿父母的出院准备度与疾病不确定感, 及时提供诸如照护知识与计划等信息支持, 转变父母异常认知, 从而为早产儿及父母顺利过渡到家庭做好准备。)